Batteries: High Dielectric, Robust Composite Protective Layer for Dendrite‐Free and LiPF6 Degradation‐Free Lithium Metal Anode (Adv. Funct. Mater. 48/2019). (26th November 2019) - Jang, Eun Kwang; Ahn, Jinhyeok; Yoon, Sukeun; Cho, Kuk Young
Abstract : In article number 1905078, Kuk Young Cho and co‐workers fabricate an organic‐inorganic composite protective layer for lithium metal anodes from a high dielectric ZrO2 and PVdF‐HFP component. This approach can serve as a solution to overcome problems in lithium metal anodes such as dendrite formation and LiPF6 salt degradation, which cause severe safety issues and capacity fading.